LuxR family transcriptional repressor YjjQ modulates the biofilm formation and motility of avian pathogenic Escherichia coli. (20th December 2022) - Fu, Dandan; Shao, Ying; Li, Jiaxuan; Wu, Jianmei; Wu, Xiaoyan; Song, Xiangjun; Tu, Jian; Qi, Kezong
Abstract: Avian pathogenic Escherichia coli (APEC) can cause the acute and sudden death of poultry, which leads to serious economic losses in the poultry industry. Biofilm formation contributes to the persistence of bacterial infection, drug resistance, and resistance to diverse environmental stress. Many transcription regulators in APEC play an essential role in the formation of biofilm and could provide further insights into APEC pathogenesis. YjjQ has an important role in the pathogenicity of bacteria by regulating the expression of virulence factors, such as flagellar and iron uptake. However, YjjQ regulates other virulence factors, and their role in the overall regulatory network is unclear. Here, we further evaluate the function of YjjQ on APEC biofilm formation and motility. In this study, we successfully constructed mutant (AE27∆ yjjQ ) and complement (AE27Δ yjjQ-comp ) strains of the wild-type strain AE27. Inactivation of the yjjQ gene significantly increased biofilm-forming ability in APEC. Scanning electron microscopy showed that the biofilm formation of the AE27 was single-layered and flat, whereas that of the AE27∆ yjjQ had a porous three-dimensional structure. Moreover, the deletion of the yjjQ gene inhibited the motility of APEC. RNA-sequencing was used to further investigate the regulatory mechanism of YjjQ in APEC. The results indicate that YjjQ regulates biofilm formation and flagellar genes in AE27∆ yjjQ . RT-qPCR shows that YjjQ affects the transcriptional levels of genes, including flagella genes ( flhD, flhC and flgE ), and biofilm formation genes ( pstA, uhpC, nikD, and ygcS ). These results confirm that the transcription regulator YjjQ is involved in APEC biofilm formation and motility, and provide new evidence for the prevention and control of APEC. Highlights: YjjQ modulates the biofilm formation and motility of avian pathogenic Escherichia coli . RNA-Seq results showed thatYjjQ regulates biofilms and flagellar genes, and the transcript levels of biofilms and flagellar-related genes were up-regulated in AE27∆yjjQ. YjjQ plays a crucial role in the biofilm formation and motility of APEC as a negative repressor.